2016
DOI: 10.1177/1535370216649261
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Orexins A and B stimulate proliferation and differentiation of porcine preadipocytes

Abstract: Orexin A (OXA) and B (OXB) are neuropeptides which regulate appetite, energy expenditure, and arousal via G-protein coupled receptors termed as OXR1 and OXR2. The aim of this study was to characterize the effects of OXA and OXB on proliferation and differentiation of porcine preadipocytes. Porcine preadipocytes express both OXRs. OXA and OXB enhance porcine preadipocyte proliferation by 54.8% or 63.2 %, respectively. OXA and OXB potentiate differentiation of porcine preadipocytes, as judged by the increased li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It was also shown that the lipoprotein lipase content of adipocytes increased significantly after approximately one-week incubation with 100 nM of either orexin A or orexin B. 87 This observation points to the ability of the orexins to increase the enzyme that degrades fat.…”
Section: Results From Animal Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…It was also shown that the lipoprotein lipase content of adipocytes increased significantly after approximately one-week incubation with 100 nM of either orexin A or orexin B. 87 This observation points to the ability of the orexins to increase the enzyme that degrades fat.…”
Section: Results From Animal Studiesmentioning
confidence: 94%
“…88 Lipoprotein lipase content was also shown to increase after incubation of WAT with orexin. 87 All of these lead to increased lipolysis, lower fat deposition, and reduction in the fat content of the body.…”
Section: Results From Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…GH (a peptide hormone) promoted the muscle growth and correlated negatively with lipogenesis (Cordoba-Chacon et al 2015). However, orexin regulated food intake and correlated positively with lipid accumulation (Wojciechowicz et al 2016). Therefore, the serum GH and orexin concentrations could partly explain the different IMF content between pig breeds.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, previous studies have shown that orexin stimulated lipid accumulation in primary rat adipocytes and 3T3-L1 cells 23 . Pruszynska-Oszmalek and co-workers reported that orexin stimulated proliferation and differentiation of porcine preadipocytes and regulated lipid metabolism 29,48 . It is noteworthy to mention that, as for orexin system and for the same reasons mentioned above, mRNA and protein levels of lipogenic factors were not correlated.…”
Section: Orexin Regulates Lipogenic Program In Chicken Hepatocytes Amentioning
confidence: 99%